¬Potensi Biduri [Calotropis gigantea (L.) W.T. Aiton] sebagai Tanaman Obat - Meutia Faradilla; Hilda Maysarah (Fakultas Farmasi Universitas Pancasila, 2019)
Calotropis gigantea (L.) W.T. Aiton or known as Biduri in Indonesia has been used in traditional medicine as an anti-inflammatory, antitoxin and antipyretic. This plant is often found in hot and arid climates. Research on the potential of this plant has not been done much in Indonesia. This article aims to examine the potential of Biduri as a source of medicinal plants. The study was carried out by reviewing research literatures of the botanical plants both sourced from international and national journals. The results of the study indicate that various types of extracts from the biduri plant have therapeutic activities for further development. The phytochemical testing and isolation has also been carried out to look for active substances that play a role in the pharmacological activity being tested. Based on the studies that have been carried out, biduri plants have great potential to be researched and further developed to become one of the sources of medicinal plants in Indonesia.